Optimization of tool wear and surface roughness in ST-37 steel turning process with varying tool angles and machining parameters - Burhanuddin, Yanuar; Harun, Suryadiwansa; Ibrahim, Gusri Akhyar; Hamni, Arinal (Jurnal Polimesin, 2024)
The process of cutting low carbon steel (ST-37) typically utilizes High-Speed Steel (HSS) tools owing to their high hardness, affordability, and ease of shaping tool geometry. In machining, tool geometry plays a crucial role in the material cutting process and determines the quality of the final product, particularly surface roughness. The objective of this research is to achieve optimal surface roughness by varying the tool geometry and nose radius. This study employed an experimental approach using ST-37 and HSS tools. The variations in tool geometry include side rake angles of 12°, 15°, and 18°; side cutting edge angles of 85°, 80°, and 75°; and nose radii of 0 mm, 0.4 mm, and 0.8 mm. The machining parameters applied consist of a cutting depth of 1 mm and 2 mm, spindle rotation speeds of 185 rpm, 425 rpm, and 624 rpm, and a feed rate of 0.05 mm/rev, 0.075 mm/rev, and 0.1 mm/rev. Tool wear measurements were captured using a USB camera, whereas the surface roughness was assessed using a surface roughness tester. The impact of the tool geometry on the surface roughness was analyzed using the Taguchi-Grey Relational Analysis (Taguchi-GRA) and ANOVA methods. The optimal combination for ST-37 lathe machining with a sharpening tool is: A1 (cutting depth 1 mm), B1 (cutting speed 17.42 m/min), C3 (feed 0.05 mm/rev), D1 (corner radius 0 mm), E3 (side rake angle γ 18°), and F3 (side cutting edge angle γ 75°). According to the Analysis of Variance (ANOVA), three factors—cutting speed, tool tip angle, and chip angle—should be considered to achieve minimal tool wear and desirable surface roughness during machining